Additional information on Mycocitrus aurantium (Bionectriaceae, Hypocreales): an unusual bamboo-inhabiting fungus found in South America - Loguercio Leite, Clarice (2018)
Mycocitrus Möller is a tropical genus that comprises two species, which form large orange stromata on bamboo culms. An ongoing survey of macrofungi in Santa Catarina State, Brazil, has produced four collections of Mycocitrus aurantium Möller. This species is considered rare and few records of it are found in the literature. The goals of this work are to improve what is known about the morphology, report the first culture and discuss the phylogenetic position of M. aurantium. Morphological and phylogenetic studies were carried out using fresh specimens and cultures. A phylogeny was constructed based on sequences of the nuclear ribosomal internal transcribed spacer. Currently, Mycocitrus is placed in the Bionectriaceae (Hypocreales); however, its placement at the family level is unclear when considering morphological characters alone.